Activity of mitogen-activated protein kinases in the esophageal epithelium of patients with Barrett's esophagus. Issue 6 (1st September 2015) - Chwiesko, A.; Baniukiewicz, A.; Semeniuk, J.; Kaczmarski, M.; Wasielica-Berger, J.; Milewski, R.; Dabrowski, A.
Summary: Barrett's esophagus (BE), a complication of gastroesophageal reflux disease, is associated with an increased risk of esophageal cancer. Mitogen-activated protein kinases may play an important role in the pathogenesis of this process. We aimed to evaluate mitogen-activated protein kinases activity in esophageal mucosa of patients with BE and find possible relationship between reflux type and BE. Twenty-four patients (mean age: 59 years) with gastroesophageal reflux disease symptoms and endoscopically suspected esophageal metaplasia (ESEM) were prospectively enrolled for testing by a multichannel intraluminal impedance monitoring along with a Bilitec 2000. Endoscopic biopsies were taken from methylene blue-positive pit patterns (sites suggesting specialized intestinal metaplasia [SIM]), from 2 cm above the Z-line and from cardial parts of the stomach. The biopsies were analyzed for extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), p38 activity by Western blot. Seventeen ESEMs had histologically proven metaplasia: eight patients had SIM and nine had gastric-type epithelia (GE). Biliary reflux was more evident in SIM ( P = 0.019) but not in GE ( P = 0.019); non-biliary reflux was typical for GE ( P = 0.005) but not for SIM ( P = 0.04). Strong activations of ERK and p38 were found predominantly in SIM, but not in normal esophageal mucosa (NE) ( P = 0.01 and P < 0.001 respectively). Strong signals for active JNK and p38 were detected in GE, but not in NE ( P = 0.006 and P = 0.02 respectively). ERK activity was significantly higher than p38 activity in ESEM patients only with GE ( P = 0.02). The strong activation of ERK, but not JNK is indicative of SIM. The presence of bile in gastroesophageal refluxate is predisposing to SIM, but not to GE in esophageal mucosa.